Asymmetric distribution of falling film solution flowing on hydrophilic horizontal round tube. (June 2017) - Ji, Ge; Wu, Jiafeng; Chen, Yaping; Ji, Guangju
Highlights: Multi-phase flow model was established for falling film flow on a horizontal tube. Both transient and steady characteristics of solution film spreading were analyzed. Liquid coverage rate increases with solution flow rate or surface wettability rise. Film thickness and film velocity are asymmetric over the horizontal tube surface. Thinnest film thickness or maximum film velocity is at circumferential angle 120°. Abstract: A two-dimension two phase flow model was established to simulate the falling film flow of LiBr solution on a horizontal hydrophilic tube with different solution sprinkle density and tube surface wettability, and the latter has been an overlook factor. The transient characteristics of solution spreading as well as steady film thickness were analyzed. The results show that a continuous film can only be obtained at sufficiently greater sprinkle density with real surface wettability, the liquid coverage of tube surface increases with the increase of sprinkle density or the decrease of static contact angle. The obvious asymmetric distributions of film thickness and film velocity over the horizontal tube surface are demonstrated in a steady state. The thinnest film thickness or maximum film velocity takes place at circumferential angle around 120°. A modified Nusselt equation for predicting the film thickness is suggested and verified by available both simulation and experimental data.